2012
DOI: 10.1242/dmm.009456
|View full text |Cite
|
Sign up to set email alerts
|

Locally expressed IGF-1 propeptide improves function in induced dilated cardiomyopathy through blockade of myocardial fibrosis and SRF-dependent CTGF induction

Abstract: SUMMARYCardiac fibrosis is critically involved in the adverse remodeling accompanying dilated cardiomyopathies (DCMs), which leads to cardiac dysfunction and heart failure (HF). Connective tissue growth factor (CTGF), a profibrotic cytokine, plays a key role in this deleterious process. Some beneficial effects of IGF1 on cardiomyopathy have been described, but its potential role in improving DCM is less well characterized. We investigated the consequences of expressing a cardiac-specific transgene encoding loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 44 publications
2
40
0
2
Order By: Relevance
“…The expression and regulation of CTGF in cardiac fibroblasts have been studied extensively [25]. Cardiomyocytes can also produce CTGF under the stimulation of transforming growth factor-β, endothelin and Ang II [5,26], which would contribute to a paracrine control of cardiac fibroblast functions [27] and regulate the surrounding ECM environment [4,5,28]. Consistent with these findings, our results demonstrated that Ang II can upregulate the expression of CTGF at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and regulation of CTGF in cardiac fibroblasts have been studied extensively [25]. Cardiomyocytes can also produce CTGF under the stimulation of transforming growth factor-β, endothelin and Ang II [5,26], which would contribute to a paracrine control of cardiac fibroblast functions [27] and regulate the surrounding ECM environment [4,5,28]. Consistent with these findings, our results demonstrated that Ang II can upregulate the expression of CTGF at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recent literature [18,36] we hypothesized that the serum response factor (SRF) is involved in the p63RhoGEF-dependent regulation of CTGF. The activation of the SRF was determined by luciferase reporter gene assays in NRCF.…”
Section: The P63rhogef-dependent Regulation Of Ctgf Involves the Serumentioning
confidence: 99%
“…There is, however, evidence that CTGF is regulated via G protein-coupled receptor activation, and angiotensin II (Ang II) as well as endothelin-1 (ET-1) have been implicated in this process [12][13][14][15][16]. With respect to downstream signaling a role of the actin cytoskeleton regulator RhoA and the serum response factor has been postulated [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic retinopathy, CTGF contributes to thickening of the retinal capillary basal lamina and is involved in loss of pericytes (Klaassen et al 2015). Interestingly, recent data suggest that downregulation of CTGF via IGF-1 signaling in dilated cardiomyopathy attenuates myocardial fibrosis and improves cardiac function (Touvron et al 2012).…”
Section: Role Of Ctgf In Age-related Vascular Pathologiesmentioning
confidence: 99%